2009
DOI: 10.1890/08-1777.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Argentine ant spread over the heterogeneous landscape using a spatially explicit stochastic model

Abstract: The characteristics of spread for an invasive species should influence how environmental authorities or government agencies respond to an initial incursion. High-resolution predictions of how, where, and the speed at which a newly established invasive population will spread across the surrounding heterogeneous landscape can greatly assist appropriate and timely risk assessments and control decisions. The Argentine ant (Linepithema humile) is a worldwide invasive species that was inadvertently introduced to New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…42) for the expansion of the Argentine ant at regional and local scales, not only among countries, is needed to assess the geographic dimensions of the invasion over time in fine detail. This type of information is crucial to anticipate the rate at which Argentine ants will spread and the areas most likely to be invaded (28,43). Finer-resolution data on patterns of commerce, which incorporate a strong historical perspective, are needed to provide a more rigorous test of the role of propagule pressure at global scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42) for the expansion of the Argentine ant at regional and local scales, not only among countries, is needed to assess the geographic dimensions of the invasion over time in fine detail. This type of information is crucial to anticipate the rate at which Argentine ants will spread and the areas most likely to be invaded (28,43). Finer-resolution data on patterns of commerce, which incorporate a strong historical perspective, are needed to provide a more rigorous test of the role of propagule pressure at global scales.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the distribution and dispersal pathways of this invasive ant (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and described the range limits at regional and global scales (20,(23)(24)(25)(26)(27)(28). However, most of these studies relied on simple environmental niche models or described the current distribution of the species using only partial records.…”
mentioning
confidence: 99%
“…Increasingly, studies have shown that human-mediated dispersal plays an important role in the long-distance dispersal of invasive terrestrial invertebrates (e.g., Gilbert et al 2004;Muirhead et al 2006;Lippitt et al 2008;Pitt et al 2009;Robinet et al 2009). Since these long-distance jumps have a low probability of occurrence and are difficult to predict, the most appropriate models to describe this type of spread are stochastic although hundreds of replicate simulations may be required to obtain a representative estimate of potential spread (Pitt et al 2009;Robinet et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Spatial stochastic models have been increasingly used for assessing risks of ecological invasions (Rafoss 2003, Cook et al 2007, Pitt et al 2009, Muirhead et al 2006, 2010. We applied a pathway model that used vector-based information stored in the NRRS database to predict movements of recreational travellers to federal campgrounds in the U.S., including cross-border visits from Canada.…”
Section: Pathway Modelmentioning
confidence: 99%